The Design, Development and Testing of Human Resource Information System (HRIS) for CSU Aparri - Liquigan, Ferdinand; Javier, Billy (International Journal of Arts, Sciences and Education, 2024)
The traditional method of managing human resources involves manual processes that are prone to inefficiencies, errors, and delays, requiring substantial time and effort to maintain. This issue significantly affects the administrative functions of human resource officer within the campus, resulting in decreased productivity and employee dissatisfaction. The project titled "Design, Development, and Testing of a Human Resource Information System (HRIS) for Cagayan State University - Aparri Campus" addresses these challenges by providing a web-based HRIS that streamlines HR functions and enhances operational efficiency. The system is designed for quick data entry and retrieval, providing a more organized and efficient means of managing personnel records. The Agile Development Model, implemented within the established framework of the System Development Life Cycle (SDLC) was used. The assessment of the HRIS developed at CSU Aparri shows it as a robust and effective system, meeting ISO 25010:2011 standards. IT experts rated it highly across compatibility, security, usability, functionality, performance stability, maintainability, and portability. Compatibility and security were particularly praised for their adaptability and stringent data protection. While usability scored slightly lower, it still indicates efficient navigation and user satisfaction. End-users reported high satisfaction, perceiving the HRIS as beneficial and expressing strong intentions to continue using it. These results affirm the HRIS’s success in meeting IT and user needs, highlighting its reliability, security, and overall effectiveness, with room for further usability enhancements. The application ultimately contributes to better decision-making and improved administrative efficiency.